Hubungan Beban Kerja dengan Tingkat Stres Perawat di Rumah Sakit UMMI Bengkulu - Julius Habibi; Anita Yuliana; Sulastri (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2026)
Background: Nurses are health professionals with high workloads that may lead to work-related stress and affect both physical and psychological health. Imbalance between workload and individual capacity can reduce performance and the quality of healthcare services. Objective: To determine the relationship between workload and stress levels among nurses at Ummi General Hospital, Bengkulu. Methods: A quantitative study with a cross-sectional design was conducted among 82 staff nurses selected using purposive sampling based on inclusion criteria. Workload was measured using the NASA Task Load Index (NASA-TLX), stress level using the Perceived Stress Scale (PSS-10), and general health condition using the General Health Questionnaire (GHQ-12). Data were analyzed using univariate analysis and bivariate analysis with the Chi-square test (α = 0.05). Results: Most nurses experienced moderate workload (81.7%) and mild stress levels (89.0%). A significant relationship was found between workload and stress level (χ² = 18.417; p = 0.000). All respondents had normal general health conditions. Conclusion: Workload is significantly associated with nurses’ stress levels. Hospitals should implement workload redistribution, optimize shift scheduling, and provide structured stress management programs to prevent chronic work-related stress. Keywords: Workload; Work stress; Nurses; Hospital.